Effect of surface finishing on the colour stability and translucency of dental ceramics - Işıl Sarıkaya; Kaan Yerliyurt; Yeliz Hayran (BMC, 2018)
Abstract Background The purpose of this study was to investigate the effects of staining solutions and surface finishing on the colour stability and translucency of hybrid ceramic (HC) and resin nanoceramic (RNC) materials. Methods Twenty four groups consisting of 10 specimens (240 specimens in total) were created out of HC and RNC, including six groups to be stored in distilled water served as the controls groups. The Vita Enamic technical set, Shofu polishers, medium and fine rubber wheels and Sof-Lex polishing discs were used as polishing instruments. Cola, tea, and coffee were used as staining solutions. The colour differences (∆E*) and translucency parameter (TP) were evaluated by a spectrophotometer. Data were analysed by a One-way Analysis of Variance (ANOVA) and Mann-Whitney U test. Results There was a statistically significant difference between the ∆E* values of the HC specimens in the coffee groups and the ∆E* values of the other HC groups (p < 0.05). The ∆E* values of the RNC specimens in the coffee and tea groups were not different from the specimens in the cola groups (p > 0.05). The TP values of the polished groups were higher than the Sof-Lex groups and the Shofu groups on both HC and RNC materials (p < 0.05). Conclusions Increased ∆E* values were observed in HC specimens stored in a coffee solution compared to the specimens stored in a tea or cola solution. Both of the RNC specimens stored in coffee and tea had higher ∆E* values than the RNC specimens stored in the cola. The TP values of both HC and RNC specimens stored in the coffee solution decreased.